Structure design and analysis of GRP Bedar / Muhammad Adam Idris - Idris, Muhammad Adam (2022)
The project's objectives were to develop and analyse a GRP Bedar boat's frame construction. A bedar boat is a traditional wood- built fishing boat. It's a boat that was made to match the shape of its own body. In this project, the Bedar boat was made out of Glass Reinforced Plastic rather than wood. Nonetheless, there are a slew of issues with finishing this assignment successfully. The design of the boat frame structure, the high degree of skill required, and the widespread use of wood in boat construction all contribute to this. This problem, however, may be overcome, and the project's objectives can be attained. One of its objectives is to improve the boat's structural strength. Apart from that, it is capable of effectively constructing a good boat construction and ensuring the boat's stability. As a result, there are stages to producing a product that must be completed in order to attainthe best results. To begin, the builders must research and learn about the boats that must be built in order to construct them using accurate specifications. They can design the boat using tools like PolyCad or Rhino. To assure the boat's safety, they must assess its strength. After that, the builder will be able to design and construct the boat construction efficiently. The boat design structure will be constructed successfully in the future. The boat's strength can be boosted as a result of the expected outcome by using GRP material and a correct boat construction.